Advances in crystal growth research - Sato, Kiyotaka, 1946-; Furukawa, Y. (Yoshinori); Nakajima, K. (Kazuo) (North-Holland, 2001)
The aim of this book is to provide a timely collection that highlights advances in current research of crystal growth ranging from fundamental aspects to current applications involving a wide range of materials. This book is published on the basis of lecture texts of the 11th International Summer School on Crystal Growth (ISSCG-11) to be held at Doshisha Retreat Center in Shiga Prefecture Japan, on July 24-29, 2001. This school is always associated with the International Conference of Crystal Growth (ICCG) series that have been held every three years since 1973; thus this school continues the tradition of the past 10 schools of crystal growth.